Introduction of DMD Method to Study the Dynamic Structures of a Three-Dimensional Centrifugal Compressor with and without Flow Control - Shuli Hong; Guoping Huang; Yuxuan Yang; Zepeng Liu (Energies, 2018)
The flow structures around the blade tip, mainly large-scale leakage vortex, exert a great influence on compressor performance. By applying unsteady jet control technology at the blade tip in this study, the performance of the compressor can be greatly improved. A numerical simulation is conducted to study the flow characteristics of a centrifugal compressor with and without a flow control. The complex flow structures cause great difficulties in the analysis of the dynamic behavior and flow control mechanism. Thus, we introduced a dynamic flow field analysis technology called dynamic mode decomposition (DMD). The global spectrums with different global energy norms and the coherent structures with different scales can be obtained through the DMD analysis of the three-dimensional controlled and uncontrolled compressors. The results show that the coherent structures are homogeneous in the controlled compressor. The leakage vortex is weakened, and its influence range of unsteady fluctuation is reduced in the controlled compressor. The effective flow control created uniform vortex structures and improved the overall order of the flow field in the compressor. This research provides a feasible direction for future flow control applications, such as transferring the energy of the dominant vortices to small-scale vortices.